Radical Depolymerization of Alginate Extracted from Moroccan Brown Seaweed Bifurcaria bifurcata - Bouissil, Soukaina; El Alaoui-Talibi, Zainab; Pierre, Guillaume; Rchid, Halima; Michaud, Philippe; El Modafar, Cherkaoui; Delattre, Cédric (Applied Sciences, 2020)
International audience The degradation of alginate extracted from Moroccan Bifurcaria bifurcata has not been fully established to date. In this work, we report the extraction and the characterization of alginate (ASBB) from the brown algae B. bifurcata, as well as the production of oligo-alginates (OGABs) by using a green chemistry process. The depolymerization of ASBB was carried out by controlled radical hydrolysis through our green chemistry process using a hydrogen peroxide (H2O2) catalyst. The molecular weight (Mw) and degree of polymerization (DP) distribution of oligo-alginates (OGABs) obtained were then characterized by HPLC size exclusion chromatography (SEC) and high-performance anion exchange chromatography with pulsed amperometric detection (HPAEC-PAD). Structural characterization revealed that after 6 h of depolymerization of ASBB, we obtained OGABs with Mw ≤ 5.5 kDa and 2 ≤ DP ≤ 24. These results highlight the effectiveness of the controlled radical hydrolysis of alginate to produce good yields of alginate fractions with controlled Mw with a known polymerization degree (DP) and without altering properties of oligo-alginates. Bifurcaria bifurcata can be a potential source of alginate and oligo-alginates given its abundance on the northwest Atlantic coast. The production and characterization of oligo-alginates promote their exploitation in the cosmetic, pharmaceutic, and agriculture fields